Efficacy and treatment satisfaction with on-demand tadalafil (Cialis) in men with erectile dysfunction - Skoumal, René; Chen, Juza; Kula, Krzysztof; Breza, Jan; Calomfirescu, Nicolae; Basson, Bruce R; Kopernicky, Vladimir (European urology, 2004)
OBJECTIVE: Tadalafil (Cialis) is an inhibitor of phosphodiesterase type 5, which mediates relaxation of vascular smooth muscle in the corpus cavernosum thus facilitating erection. The purpose of this multicentre, randomized, double-blind, parallel group, placebo-controlled study was to evaluate efficacy and treatment satisfaction of on-demand Cialis in men with mild-to-severe erectile dysfunction (ED). METHODS: Following a 4-week treatment-free run in period, patients stratified into three severity groups by the International Index of Erectile Function (IIEF) Erectile Function (EF) domain score were randomized to receive either placebo or Cialis 20 mg taken on demand over a 12-week period. Efficacy endpoints were change from baseline in IIEF EF domain scores, responses to Sexual Encounter Profile diary (SEP) questions, and responses to the Global Assessment Questions (GAQ). Treatment satisfaction was evaluated using the Erectile Dysfunction Inventory of Treatment Satisfaction (EDITS) questionnaire in two of seven participating countries where validated translations were available. RESULTS: Of the 443 men who entered the trial, 409 (mean age, 52 years) formed the intent-to-treat population. Mean baseline demographics and ED severity measures were balanced between treatment groups except for a higher percentage of patients naïve to sildenafil in the tadalafil group compared to placebo (50% versus 36%). The percentage of patients in each IIEF EF severity class (mild, moderate and severe) was 47%, 30% and 23% for placebo patients and 48%, 29% and 23% for tadalafil patients, respectively. Tadalafil was significantly superior to placebo on all primary efficacy measures (IIEF EF domain scores, SEP15, GAQ1; p < 0.001); notably 64% of tadalafil patients achieved a normal IIEF EF domain score at endpoint compared to 16% of placebo patients (p < 0.001). Of the 185 patients completing the EDITS questionnaire (137 receiving Cialis and 48 receiving placebo), tadalafil-treated patients had a median EDITS score of 84 (95%CI 80, 86), which was significantly higher than the median score for placebo-treated patients of 41 (95%CI 32, 59; p < 0.001; Wilcoxon test). The proportion of patients satisfied with treatment (defined as final EDITS score greater than 50) was 87% for the tadalafil-treated group and 46% for the placebo-treated group (p < 0.001; exact test). Adverse events were significantly more common with tadalafil than placebo (p < 0.01) and included primarily headache (7.2% versus 1.9%) and flushing (4.6% versus 0%). One patient discontinued tadalafil treatment due to back pain. CONCLUSION: In men with mild-to-severe ED, tadalafil 20 mg significantly improves erectile function, demonstrates superior treatment satisfaction relative to placebo, and is well tolerated. This is the first study to yield efficacy data on tadalafil in an Eastern European population of men with erectile dysfunction, and the first to measure satisfaction with the EDITS questionnaire in any study population of men with this condition using tadalafil.
Keywords: tadalafil; Patient Satisfaction; Aged; Carbolines; Treatment Outcome; Aged, 80 and over; stupeň závažnosti nemoci; lidé středního věku; senioři; Severity of Illness Index; Erectile Dysfunction; lidé; Vasodilator Agents; Adult; Middle Aged; dospělí; Europe; vazodilatancia; výsledek terapie; senioři nad 80 let; karboliny; Male; Humans; mužské pohlaví; Double-Blind Method; erektilní dysfunkce; spokojenost pacientů; Tadalafil; Evropa; dvojitá slepá metoda